Synthesis and biological potential of 1,2,4-triazole derivatives with a 2-bromo-5-methoxyphenyl fragment - Skoryi, M. P.; Shcherbyna, R. O.; Salionov, V. O.; Щербина, Роман Олександрович; Саліонов, Володимир Олександрович (Запорізький державний медико-фармацевтичний університет, 2023)
The purpose of the work is the purposeful synthesis of new promising substances - derivatives of 1,2,4-triazole-3-thiones containing an aromatic substituent in their structure, the study of biological activity, as well as the establishment of regularities between the chemical structure and pharmacological action of the synthesized compounds.
Keywords: тези доповідей